An effective and recyclable deproteinization method for polysaccharide from oyster by magnetic chitosan microspheres. (1st September 2018) - Song, Zhuoyue; Hu, Youdong; Qi, Longkai; Xu, Tingting; Yang, Yongsheng; Xu, Zhanchi; Lai, Xiaoping; Wang, Xiaoli; Zhang, Danyan; Li, Shijie
Highlights: MCM adsorption method presented high deproteinization ratio and recovery ratio. MCM adsorption is a physical adsorption process with high protein selectivity. MCM can be reused by regeneration. Abstract: The aim of this study was to synthesize magnetic chitosan microspheres (MCM) for the deproteinization of crude polysaccharides from Ostrea rivularis Gould (ORP), and evaluate their adsorption properties. Firstly, MCM were synthesized by microemulsion process. Then they were characterized by Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD) and vibrating-sample magnetometer (VSM). At last, MCM was applied as a magnetic separable adsorbent for deproteinization of ORP. The results showed that MCM had smooth surface with particle diameter of 2–6 μm. The adsorption kinetics and adsorption isotherms were well fitted by the pseudo-second order equation and the Freundlich equation, respectively. Comparing with the Sevag method, MCM exhibited higher deproteinization ratio, higher polysaccharides recovery, and miner pollution. In addition, the deprotenaization capacity can be regenerated. Therefore, MCM would be used as promising adsorbents for the deproteinization of polysaccharides.